2013
DOI: 10.4172/2157-7471.1000184
|View full text |Cite
|
Sign up to set email alerts
|

A Species-Specific PCR Based Assay for Rapid Detection of Mango Anthracnose Pathogen Colletotrichum gloeosporioides Penz. and Sacc

Abstract: Mango (Mangifera indica L.) a fruit of nutraceutical value is accepted as the most eatable fruit crop worldwide. Mango production has been severely affected by several biotic stress mainly diseases and anthracnose is the major post-harvest disease of mango results in heavy losses. The present investigation describes PCR based assay for rapid and sensitive detection of Colletotrichum gloeosporioides causing mango anthracnose. Genus specific universal primer pair ITS1 and ITS4 was employed to amplify Colletotric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
(16 reference statements)
1
18
0
Order By: Relevance
“…The primers amplified a fragment corresponding approximately to 560 bp for the C. gloeosporioides isolates. These results were in line with the earlier findings of Xiao et al (2004) and Kamle et al (2013). Pandey et al (2012) amplified the genomic DNA from 12 isolates of C. gloeosporioides belonging to different regions by PCR with C. gloeosporioides species-specific primers.…”
Section: Field Efficacy Testssupporting
confidence: 92%
See 2 more Smart Citations
“…The primers amplified a fragment corresponding approximately to 560 bp for the C. gloeosporioides isolates. These results were in line with the earlier findings of Xiao et al (2004) and Kamle et al (2013). Pandey et al (2012) amplified the genomic DNA from 12 isolates of C. gloeosporioides belonging to different regions by PCR with C. gloeosporioides species-specific primers.…”
Section: Field Efficacy Testssupporting
confidence: 92%
“…The rDNA region of ITS1 and ITS4 were amplified in ten isolates of C. gloeosporioides by polymerase chain reaction (PCR) (White et al 1990;Stracieri et al 2016). The PCR amplifications of DNA were performed with a program consisted of following condition for C. gloeosporioides: an initial step of 5 min at 94°C, followed by 30 cycles of denaturation at 94°C for 60 sec, annealing at 58°C for 2 min, extension at 72°C for 60 sec and a final extension at 72°C for 5 minutes (Kamle et al, 2013). The C. gloeosporioides species specificity was confirmed using species specific primer MKCgF 5`TTGCTTCGGCGGGTAGGGTC3` and MKCgR 3`ACGCAAAGGAGGCTCCGGGA5` (Kamle et al, 2013).…”
Section: Morphological and Molecular Characterization Of Colletotrichmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have been carried out to resolve the issue of species complex in Colletotrichum spp. in different areas of the world on various hosts like mango (Kamle et al, 2013 ), guava (Mohd Anuar et al, 2014 ), herbaceous plants (Photita et al, 2005 ), soursop (Álvarez et al, 2014 ), and also in medicinal plants as endophytes (Lima et al, 2012 ) using molecular marker analysis.…”
Section: The Pathogen- Colletotrichum Capsicimentioning
confidence: 99%
“…variable ITS regions -especially the ITS1 portion -provides sufficient information to infer phylogenetic relationships among Colletotrichum species [21]. Kamle et al [22] reported that DNA fragment of approximately 580 bp were amplified for C. gloeosporioides using ITS (Internal Transcribed spacer) primer. The Colletotrichum isolates were identified using PCR with species specific primers, complemented by phylogenetic analysis of nucleotide sequences of the internal transcribed spacer region and partial glyceraldehyde-3-phosphate dehydrogenase gene [23].…”
Section: Pcr Amplification and Sequence Analysismentioning
confidence: 99%